0
$\begingroup$

I have solved two limits, but only found one answer while the solution contains two. What am I missing?

First limit

$$\lim_{x\to\infty} \sqrt{x(x+a)}-x = \lim_{x\to\infty} \sqrt{x^2(1+\frac{a}{x}})-x = \lim_{x\to\infty} x(\sqrt{(1+\frac{a}{x}})-1) = \lim_{x\to\infty} \frac{x(\sqrt{1+\frac{a}{x}}-1) (\sqrt{1+\frac{a}{x}}+1)}{(\sqrt{1+\frac{a}{x}}+1)} = \lim_{x\to\infty} \frac{a}{(\sqrt{1+\frac{a}{x}}+1)} = \frac{a}{2}$$

However, $+\infty$ is also an answer?

Second limit

$$\lim_{x\to\infty} x(\sqrt{x^2+1}-x) = \lim_{x\to\infty} \frac{x(\sqrt{x^2+1}-x)(\sqrt{x^2+1}+x)}{(\sqrt{x^2+1}+x)} = \lim_{x\to\infty} \frac{x}{(\sqrt{x^2+1}+x)}$$

But $x\to\infty$ so we can say $\sqrt{x^2+1} \approx \sqrt{x^2}$, which gives:

$$ = \lim_{x\to\infty} \frac{x}{|x|+x} = \lim_{x\to+\infty} \frac{x}{2x} = \frac{1}{2}$$

But it should also be $-\infty$.

$\endgroup$
  • 1
    $\begingroup$ Your two answers look fine. Where do $\infty$ and $-\infty$ come from? $\endgroup$ – Olivier Oloa Jul 26 '16 at 13:49
  • $\begingroup$ From the answers in my course book. We don't get the full solution though, so I don't know how they got to them. $\endgroup$ – Aaron Jul 26 '16 at 13:53
  • $\begingroup$ The $-\infty$ for the second limit is definitely wrong because the expression is positive for $x>0$ $\endgroup$ – Peter Jul 26 '16 at 13:58
  • 1
    $\begingroup$ I don't see how you did the first one. Specifically, the first equality $$\lim_{x \to \infty} x\left( \sqrt{x(x+a)} -x \right) = \lim_{x\to \infty} x\left( \sqrt{1 + \tfrac a x} - 1 \right).$$ It seems you lost a factor of $x$ somewhere. I think that limit should be infinite. $\endgroup$ – User8128 Jul 26 '16 at 13:59
  • 1
    $\begingroup$ @Peter Yes, but I introduced the $+\infty$ myself, maybe there is another possibility when $x\to-\infty$? $\endgroup$ – Aaron Jul 26 '16 at 14:14
1
$\begingroup$

Hint:

The first factorisation is false if $x<0$: $$\sqrt{x(x+a)}-x = \sqrt{x^2\Bigl(1+\frac{a}{x}\Bigr)}-x=\lvert x\rvert\sqrt{1+\frac{a}{x}}-x=\begin{cases}x\biggl(\sqrt{1+\dfrac{a}{x}}-1\biggr)&\text{if }x>0,\\-x\biggl(\sqrt{1+\dfrac{a}{x}}+1\biggr)&\text{if }x<0.\end{cases}$$

$\endgroup$
  • $\begingroup$ Sorry, there was a typo at the start, the x in the beginning. Just edited that. $\endgroup$ – Aaron Jul 26 '16 at 14:08
  • $\begingroup$ @Bernard .since $x\to \infty$ we shall concentrate only in the neighborhood where $x>0$ .so you need not define your second case that is x<0 $\endgroup$ – Sathasivam K Jul 26 '16 at 14:20
  • 1
    $\begingroup$ For me, $x\to\infty$ comprises both $+\infty$ and $-\infty$. $\endgroup$ – Bernard Jul 26 '16 at 14:30
  • $\begingroup$ OK sir.I think you assumed $\infty$ to be either + or - infinity,Right? $\endgroup$ – Sathasivam K Jul 26 '16 at 14:33
  • 1
    $\begingroup$ Yes. I don't write the sign only in the case it's clear from the contest (e.g. sequences, for wich the variable is a natural integer). $\endgroup$ – Bernard Jul 26 '16 at 14:34
1
$\begingroup$

Setting $1/x=h,$ $$\lim_{x\to\infty} \sqrt{x(x+a)}-x=\lim_{h\to0^+}\dfrac{\sqrt{1+ah}-1}h=\lim_{h\to0^+}\dfrac{1+ah-1}{h(\sqrt{1+ah}+1)}=\dfrac a{\sqrt1+1}\text{ for finite }a$$

Setting $1/x=h,$ $$\lim_{x\to\infty} x(\sqrt{x^2+1}-x) =\lim_{h\to0^+}\dfrac{\sqrt{1+h^2}-1}{h^2}$$

$$=\lim_{h\to0^+}\dfrac{1+h^2-1}{h^2(\sqrt{1+h^2}+1)}=\dfrac1{\sqrt1+1}=?$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.